Ciglitazone Inhibits Plasmin-Induced Proinflammatory Monocyte Activation via Modulation of p38 MAP Kinase Activity - Syrovets, Tatiana; Schüle, Almut; Jendrach, Marina; Büchele, Berthold; Simmet, Thomas (Thrombosis and Haemostasis, 2002)
Plasmin triggers chemotaxis and NF-κBand AP-1-mediated proinflammatory gene expression in human peripheral monocytes (PM). Compared with macrophages and dendritic cells, PM express mainly the peroxisome proliferator-activated receptor (PPAR) γ and traces of PPARα as detected by semiquantitative RT-PCR and immunoblotting. The PPARγ agonist ciglitazone, but not the PPARα agonist clofibric acid, concentration-dependently inhibited the plasmin-, but not the FMLP-induced PM chemotaxis. Similarly, release of interleukin (IL)-1α, IL-1β and tumor necrosis factor (TNF)-α from plasmin-stimulated PM was concentration-dependently inhibited by ciglitazone, but not by clofibric acid, while the LPS-induced TNF-α release remained unaffected by any of both PPAR agonists. Ciglitazone activates PPARγ as shown by a novel surface plasmon resonance analysis and inhibits the plasmin-induced activation of NF-κB and AP-1. It also inhibits p38 MAPK phosphorylation essential for the plasmin-induced PM chemotaxis and gene activation. Thus, activation of PPARγ by ciglitazone may allow controling of the plasmin-mediated recruitment and activation of PM at sites of inflammation.
Keywords: Monocytes/macrophages; cytokines; chemotaxis; transcription factors; p38 MAPK